Koor Industries and Crafts Co. Ltd. Haifa : fourth report : 1-4-1948 - 31-3-1948. (Haifa, 1949)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: metaalnijverheid; glasindustrie; economie; Palestina; Israël